Production of biologically active human interleukin-10 by Bifidobacterium bifidum BGN4 - Hong, Nayoun (Microb Cell Fact, 2021)
BACKGROUND: Bifidobacterium spp. are representative probiotics that play an important role in the health of their hosts. Among various Bifidobacterium spp., B. bifidum BGN4 exhibits relatively high cell adhesion to colonic cells and has been reported to have various in vivo and in vitro bio functionalities (e.g., anti-allergic effect, anti-cancer effect, and modulatory effects on immune cells). Interleukin-10 (IL-10) has emerged as a major suppressor of immune response in macrophages and other antigen presenting cells and plays an essential role in the regulation and resolution of inflammation. In this study, recombinant B. bifidum BGN4 [pBESIL10] was developed to deliver human IL-10 effectively to the intestines. RESULTS: The vector pBESIL10 was constructed by cloning the human IL-10 gene under a gap promoter and signal peptide from Bifidobacterium spp. into the E. coli-Bifidobacterium shuttle vector pBES2. The secreted human IL-10 from B. bifidum BGN4 [pBESIL10] was analyzed by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE), Western Blotting, and enzyme-linked immunosorbent assay (ELISA). More than 1,473 ± 300 ng/mL (n = 4) of human IL-10 was obtained in the cell free culture supernatant of B. bifidum BGN4 [pBESIL10]. This productivity is significantly higher than other previously reported human IL-10 level from food grade bacteria. In vitro functional evaluation of the cell free culture supernatant of B. bifidum BGN4 [pBESIL10] revealed significantly inhibited interleukin-6 (IL-6) production in lipopolysaccharide (LPS)-induced Raw 264.7 cells (n = 6, p < 0.0001) and interleukin-8 (IL-8) production in LPS-induced HT-29 cells (n = 6, p < 0.01) or TNFα-induced HT-29 cells (n = 6, p < 0.001). CONCLUSION: B. bifidum BGN4 [pBESIL10] efficiently produces and secretes significant amounts of biologically active human IL-10. The human IL-10 production level in this study is the highest of all human IL-10 production reported to date. Further research should be pursued to evaluate B. bifidum BGN4 [pBESIL10] producing IL-10 as a treatment for various inflammation-related diseases, including inflammatory bowel disease, rheumatoid arthritis, allergic asthma, and cancer immunotherapy.